Leadership styles and employee work-life balance: A systematic literature review - Batubara, Rizkinta Amelia; Mujib, Abdul (INSPIRA: Indonesian Journal of Psychological Research, 2025)
This systematic literature review examines the relationship between leadership styles and employee work-life balance (WLB). Following the PRISMA protocol, data were collected from four academic databases (Publish or Perish/Google Scholar, Scopus, Emerald Insight) using the PICO framework. From an initial pool of 296 articles, 31 studies met the inclusion criteria for analysis. The findings consistently demonstrate that transformational leadership exerts a significant positive influence on WLB by fostering a supportive work environment, providing psychological resources, and promoting flexible work arrangements. Supportive and authentic leadership styles also show positive correlations, while authoritarian leadership is consistently detrimental. The review identifies perceived organizational support and flexible work policies as key mediating factors. The results underscore that effective, people-oriented leadership is crucial for cultivating organizational cultures that support employee well-being and sustainable work-life integration. Organizations are advised to develop leadership training programs that focus on empathy, flexibility, and empowerment. This study contributes to the literature by synthesizing evidence across diverse contexts and suggests that future research should explore causal relationships and the moderating role of cultural and organizational variables.